Overweight and obesity in college students: prevalence and associated factors - Barros, Gerleison Ribeiro (2021)
The aim of this study was to estimate the prevalence of overweight and obesity and their associations with physical activity and sitting time among men and women university students in Minas Gerais, Brazil. This is a cross-sectional study that estimated the outcomes of overweight (BMI: 25.0 to 29.9 kg/m2) and obesity (BMI: ≥30.0 kg/m2) using the body mass index (BMI) by self-reported body mass and stature. The independent variables were physical activity and sitting time, and control variables were sociodemographic, link with the university and behavioral variables were included in three models. Association analyzes were performed via Odds Ratio (OR) using Multinomial Logistic Regression. The significance level was 5%. A total of 1,105 university students participated in the study, comprising 61.6% of women. The mean age was of 21.25 (SD = 4.1) and 21.83 (SD = 4.2) for women and men, respectively. The prevalence of overweight and obesity in men was 27.5% and 6.9% and in women 15.5% and 8.0%, respectively. Time sitting was associated with obesity in men, regardless of sociodemographic characteristics (OR = 3.54; 95%CI: 1.04 – 12.12) and university stage plus sociodemographic characteristics (OR = 3.48; 95%CI: 1.01 - 11.99). With the adjustment of health behaviors, the association was not observed (OR = 3.49; 95%CI: 0.99 – 12.23). For women, no significant associations were found. In conclusion, overweight prevalence was high in men. The university men with sitting time higher represented more chances of obesity.